Clinical and regulatory considerations for novel electrophysiology mapping systems: Lessons from FIRM. Issue 12 (24th October 2018) - Wann, Daniel; Waks, Jonathan W.; Kramer, Daniel B.
Abstract: Atrial fibrillation (AF) presents a growing clinical and public health burden for which better rhythm control therapies are needed. Focal impulse and rotor mapping (FIRM), currently marketed as a part of the Topera Rotor Mapping system (Abbott Laboratories, Austin, TX, USA), represents a potentially transformational approach to guide the invasive treatment of AF. However, many years after its initial marketing clearance, the clinical utility of this technology remains uncertain. In this article, we review the scientific rationale for this novel approach to AF ablation, evaluate the current clinical evidence for FIRM‐guided ablation, and characterize its premarket regulatory assessment. Lessons for clinicians considering adoption of newly marketed mapping systems are presented.